Concepts and Contexts: The Interplay of Philosophy and History in Understanding Human Society - Rashid Manzoor Bhat; Silllalee A/L S. Kandasamy (East Asian Journal of Multidisciplinary Research, 2023)
The present study aims to investigate the historical development of philosophical thought and its impact on the interpretation of historical events and processes, identify key philosophical concepts that have influenced historical methodology, and explore the ways in which historical events and societal changes have shaped philosophical thought and discourse. Employing a combination of descriptive, analytical, and historical research methods, the study utilises a comprehensive literature review, content analysis, case study examination, and interviews with philosophers and historians to address these objectives. The findings of this study reveal the crucial role that interdisciplinary approaches play in understanding the interdependence of philosophy and history, showcasing the significance of their mutual influence.